REE Speciation in Fluoride-Carbonate-Chloride Cooling Hydrothermal Fluids in the Presence of Barite and Celestine (Thermodynamic Modeling) - Shironosova Galina; Prokopyev Ilya (Russian Journal of Earth Sciences, 2023)
A thermodynamic study was carried out in order to determine the forms of transport for the entire series of lanthanides and their ratio with changing parameters of a hydrothermal fluid of moderate concentrations of chloride, carbonate and fluoride components. Hydrothermal solution, cooling from 500 to 100 ∘C, affected barite and celestine, which are used as a source of sulfate sulfur, monazite as a source of rare earth elements (REE) and phosphorus, and calcite as a source of calcium. It has been established that, under weakly acidic (pH about 4.1) conditions, the equilibrium mineral association is represented by rare earth fluorite, monazite, rare earth fluorapatite, and strontiobarite. In the high-temperature region for light and medium REE, the leading is the first chlorocomplex LnCl+2. For heavy REE, the second fluorine complex LnF+2 takes the first place, except for terbium and dysprosium, for which a sharp predominance of the sulfate complex is revealed. A special picture is observed at 100 ∘C: the leading position is occupied by Ln+3 for both light and heavy REE. In the case of a near neutral weakly alkaline fluid (pH about 7.1), the equilibrium mineral association is represented by calcite, monazite, REE-fluorite, REE-fluorapatite, strontiobarite, and strontianite. The appearance of the latter in natural associations may serve as an indication of the increased alkalinity of the ore-forming environment. In an equilibrium weakly alkaline fluid up to 200 ∘C, hydroxocomplexes are prevalent for all REEs with the ratio Ln(OH)03> Ln(OH)+2. The first chloro complex for light REE at 500–400 ∘C, and the second fluoro complex for medium and heavy REEs follow them. At 100 ∘C, the concentration of hydroxocomplexes sharply decreases, and fluorine and carbonate complexes come to the fore. In general, there is an increased stability of the first chlorocomplex in the high-temperature region, and with decreasing temperature, the role of REE fluorocomplexes increases. Two variants of acidity-alkalinity calculations presumably correspond to modeling of two types of fluids: greisenizing – weakly acidic and carbonatite-forming – weakly alkaline.